Extracting bioactive compounds from Moringa oleifera leaves for anticancer product - Ali, Eman N. (2017)
Cancer is one of the most dangerous illness in the world. It occurs when cells in the body divide at an uncontrolled rate which then produces lumps or masses of tissue known as tumour. In addition, it affects the digestive, nervous and circulatory systems, these tumours also produce hormones which disrupts body functions. A benign tumour which remains in the same spot is harmless. On the contrary, a malignant tumour is dangerous as it may destroy healthy cells. These malignant tumours spread to healthy cells through the blood or lymphatic system. This condition is known as metastasis. Nowadays, various modern cancer treatments are available including surgery, drugs, chemotherapy, radiation therapy, steroid medications, and hormonal therapy. However, there are numerous side effects that arise from these modern treatments such as heart, lung, endocrine system, bone, joint, soft tissue, brain, spinal cord, nerve, memory, dental, vision and digestion problems. Moreover, the patient may suffer from emotional difficulties, fatigue as well as develop secondary type of cancer. In order to prevent side effects which arise from modern cancer treatments, a more natural approach with no detrimental effects to human health is required to combat cancer. The objectives of this research is to extract the bioactive compounds from the leaves of Moringa oleifera and to test the effect of the extracted material on cancer cells. In this study, the bioactive compounds from Moringa oleifera leaves is extracted using two methods which are the Soxhlet extraction method using ethanol, 2-propanol, acetone, petroleum ether and water solvent and the soaking method using ethanol and boiling water as solvent. Sample S2 which employed the Soxhlet extraction technique using water as the solvent exhibited significant cytotoxic activity against the human breast adenocarcinoma cancer cell line (MCF-7) in a concentration dependent manner with an IC50 value of 81.77±6.05μg/mL. The other samples showed no cytotoxic activity.